Cultural ecosystem services contribution to campus courtyard for students’ learning environment - Rosli, Nur Diana Shafikha; Harun, Nor Zalina (IIUM Press, 2017)
Universities today have been planned and developed with the presence of open spaces which help to attain the university goal of being a conducive learning environment. This study focuses on the physical development plan of campus courtyards as an effective outdoor feature in shaping student life. It is seen as a step to promote a sustainable living and a better learning environment. With the motto of ‘Garden of Knowledge and Virtue’, with courtyards as one of the compulsory components of the campus design, this research project selected International Islamic University in Malaysia (IIUM) as a case study. Being one of the major open space components, the research contends that courtyards on campuses also provide students with a healthy ecosystem, cultural services and a variety of benefits from nature. Nonetheless, there are weaknesses and limitations to the landscape design and planning of courtyards. A preliminary survey shows that less attention was paid to preparing courtyards as outdoor learning areas, resulting to less community engagement whilst remain as an unused space on campus. Therefore, this study aims to explore the contribution of cultural ecosystem services towards the physical characteristics of a campus courtyard as a students learning environment. Three objectives have been formulated in order to achieve the aim; to study the contribution of cultural ecosystem services provided by campus courtyards, to investigate the physical characteristics of the campus courtyard as a student learning environment and to recommend design guidelines for campus courtyards to support learning activities. The study employed a mixed-method approach which consisted of a survey questionnaire, a site inventory and observation. A survey questionnaire was distributed to 400 students from the six faculties in IIUM. The site inventory implies a checklist on three aspects which are design of courtyard, activities and students behaviour and natural elements.